KONDISI RUMAH PENDERITA KUSTA DI WILAYAH KERJA PUSKESMAS PEGIRIAN SURABAYA TAHUN 2015 - Lutfia Sekar Arum; Umi Rahayu; S. B. Ekowarno (Poltekkes Kemenkes Surabaya, 2015)
Leprosy is contagious diseaes that cannot be solved optimally in Surabaya, this compounded by stillmany densely population area that is uninhabitable. Housing and environments conditions that donot meet health requirements are risk factors for leprosy transmission source. In the work area ofPegirian Community Health Center of Surabaya in 2014 they are 17 Lepers.This research aims todescribe house physical condition of lepers.The type of research is descriptive with observational approach. The data collection is done bymeasurement and observation, the amount taken of samples is 17 houses lepers. The collecteddata is analysis descriptively with descriptions explanation based on the Decree of Ministry ofHealth of republic of Indonesia No. 829 Year 1999 regarding healthy houserequirements.The result showed that ventilation of studied lepers’ house is ineligible 94.12%. The temperatureof the houses that does not qualify is 41.17%.Humidity which is not qualified is 47.05%. 100%natural lighting of lepers’ house is ineligible. Lepers’ house which is densely populated is 94.25%,the condition of floor does not qualify is 29.41%. The suggestion is open a window, then sunlight can get into house, and install the glass tile Always keep the house clean.